Research on fluid mobility in tight-sandstone with a NMR fractal theory pore classification method - Gao, Yongli; Li, Teng; Zhang, Zhiguo; Yu, Jian; Zhang, Yingke; Li, Xuan; Zhao, Hui (Frontiers in Earth Science, 2023)
The fluid mobility characteristics in the pores with various apertures for tight-sandstone would finally determine the fluid mobility and production of tight oil and gas reservoirs. In this study, the tight-sandstone core samples collected from Middle Jurassic Xishanyao Formation in Santanghu Basin were launched the fluid mobility measurements under various centrifugal speeds. With the NMR fractal theory pore classification method, the various types of pores in the tight-sandstone core samples were classified, and the fluid mobility in different types of pores were also investigated. The results show that the tights-sandstone core samples were significantly influenced by compaction, and the core samples are relatively dense, the mineral intergranular solution pores and colloidal intergranular pores are the main storage spaces. With a constant increase of the centrifugal speed, the fluid mobility increases continuously, and the fluid mobility for CTOS-19 features stronger than that of CTOS-7, which is related to the complexity of pore structure in tight-sandstone sample. Compared with the pore aperture in CTOS-19, the pore aperture in CTOS-7 is smaller, and the connectivity between the smaller and larger pores is poorer, leading to the poorer fluid mobility. Besides, the NMR fractal theory pore classification method also shows that the COTS-7 features more pore types than COTS-19, five and four types respectively. The type P2 and P3 pores are dominant in COTS-7 and CTOS-19 core samples, and the connectivity between type P2 and P3 pores contributes dominantly to the fluid mobility. With the NMR fractal theory pore classification method, the complexity of the distribution of fluid and fluid mobility in tight reservoirs could be studied quantitatively, and the results can efficiently guide the development of residual oil and gas in tight oil reservoirs.